2011
DOI: 10.7885/1946-651x.1064
|View full text |Cite
|
Sign up to set email alerts
|

Japan’s Model of Mobile Ecosystem Success: The Case of NTT DoCoMo

Abstract: obile technologies have grown tremendously in the past ten years. In the United States in 1999 there were 36.7 users per 100 people (Akiyoshi & Ono, 2008). In 2005, there were 94,745,000 mobile phone subscribers in Japan and 201,650,000 mobile phone subscribers in the United States, while in 2009 Japan's mobile phone subscribers grew to 107,490,000 subscribers and the United States grew to 285,610,580 million subscribers, a growth rate of 13.5% in Japan and 41.8% in the United States. Interesting enough, most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Therefore, attitude is the one of the main drivers of users’ continuous desire ( Daragmeh et al, 2021 ). In addition, this study echoes with previous studies which found that attitude had a strong impact on continuance intention ( Black, 2005 ; Amoroso and Ogawa, 2011 ; Cheng, 2011 ). Thus, the participants of this study have positive attitude in using Apple Watch for guided respiration and are willing to continue using the product.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, attitude is the one of the main drivers of users’ continuous desire ( Daragmeh et al, 2021 ). In addition, this study echoes with previous studies which found that attitude had a strong impact on continuance intention ( Black, 2005 ; Amoroso and Ogawa, 2011 ; Cheng, 2011 ). Thus, the participants of this study have positive attitude in using Apple Watch for guided respiration and are willing to continue using the product.…”
Section: Resultssupporting
confidence: 88%
“…Previous studies have also indicated that users are found to have a positive attitude when they believe that the technology they use will improve their productivity ( Chau and Hu, 2001 ). Attitude has been found to be a strong determinant of continuance intention ( Black, 2005 ) and other studies related to technology have also confirmed that attitude has a strong impact on continuance use intention ( Amoroso and Ogawa, 2011 ; Cheng, 2011 ). Therefore, the following hypothesis was proposed:…”
Section: Methodsmentioning
confidence: 76%
“…Continuance intention (CI) (Bhattacherjee et al, 2008); Amoroso and Ogawa (2011);Cho et al, 2019 CI1: I intend to use an e-learning system for my university class CI2: If I have an opportunity, I will attend classes through the e-learning system CI3: I intend to keep using the e-learning system CI4: I intend to continue using the e-learning system for unceasing academic progress during COVID-19…”
Section: Author Contributionsmentioning
confidence: 99%
“…JR East has launched a mobile app application that has six services, including train guide, ticket booking, station guidance, running train information list, real-time departure information guidance and current train travel position. It can provide real-time travel position information of main trains in 22-line areas (including Shinkansen) within 100 kilometers of Tokyo Circle (Amoroso & Ogawa, 2011).…”
Section: Railways In Switzerland 231 Development Strategymentioning
confidence: 99%